Case report: Occult Listeria monocytogenes invasion leading to prosthetic hip joint infection in a patient with rheumatoid arthritis taking tofacitinib - Deng, Chaowen; Chiu, Kelvin Hei-Yeung; Lou, Nan; Xing, Fanfan (Frontiers in Medicine, 2024)
It has been suggested that targeted therapy may potentially increase the risk of listeriosis. However, no reported cases of Listeria monocytogenes prosthetic joint infection have been documented during Janus Kinase (JAK) pathway inhibitor use.Herein, we present a 70-year-old female with rheumatoid arthritis who had undergone bilateral hip joint replacement and subsequently developed Listeria monocytogenes prosthetic joint infection following tofacitinib therapy. We suggest that the use of tofacitinib may potentially heighten susceptibility to listeriosis in patients afflicted with rheumatoid arthritis.